2021
DOI: 10.1101/2021.07.19.452953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CHOmpact: a reduced metabolic model of Chinese hamster ovary cells with enhanced interpretability

Abstract: Metabolic modelling has emerged as a key tool for the characterisation of biopharmaceutical cell culture processes. Metabolic models have also been instrumental in identifying genetic engineering targets and developing feeding strategies that optimise the growth and productivity of Chinese hamster ovary (CHO) cells. Despite their success, metabolic models of CHO cells still present considerable challenges. Genome scale metabolic models (GeMs) of CHO cells are very large (>6000 reactions) and are, therefore,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…The affected pathways are not independent of each other but rather interconnected. [ 42 ] Metabolites such as histidine, phenylalanine, tyrosine, and tryptophan, found within these metabolic pathways, could serve as novel target nutrients to enhance culture performance. These amino acids, vital for cell growth and productivity in other CHO cell lines, warrant further investigation to ascertain their role in the cell line utilized in this research.…”
Section: Resultsmentioning
confidence: 99%
“…The affected pathways are not independent of each other but rather interconnected. [ 42 ] Metabolites such as histidine, phenylalanine, tyrosine, and tryptophan, found within these metabolic pathways, could serve as novel target nutrients to enhance culture performance. These amino acids, vital for cell growth and productivity in other CHO cell lines, warrant further investigation to ascertain their role in the cell line utilized in this research.…”
Section: Resultsmentioning
confidence: 99%
“…[ 83 ] The most recent version of CHO‐GSMM [ 32 ] was generated by combining previous models. By comparing the updated global CHO‐GSMM, two cell line specific CHO‐GSMMs and a recently published reduced CHO‐model, [ 84 ] it was shown that the reduced models predict core metabolic functions more precisely, whereas essential gene identification is more accurate in the cell line specific models. [ 32 ] Despite the comprehensive comparison, the impact of selecting the most suitable objective function for phenotype prediction remains to be investigated.…”
Section: Approaches For Process Optimization Using Constraint‐based M...mentioning
confidence: 99%
“…An important contribution to the field of cell line and metabolic engineering is provided by Strain et al (2023) with a review on the current state of CHO genome‐scale metabolic models (GEM), their inability to model intracellular metabolism and capture extracellular phenotypes. In addition, Jiménez del Val et al (2023) presented an improved GEM, iCHO2441, as well as two cell line‐specific GEMs for CHO‐S and CHO‐K1 that may serve as foundations for better design and assess next‐generation flux analysis techniques. Jiménez del Val et al (2023) propose a more compact network model, CHOmpact, that can provide improved interpretations from simulations, including the identification of shifts in key metabolic behaviors.…”
Section: Improving Cho Cell Line Performance Through Cell and Bioproc...mentioning
confidence: 99%
“…In addition, Jiménez del Val et al (2023) presented an improved GEM, iCHO2441, as well as two cell line‐specific GEMs for CHO‐S and CHO‐K1 that may serve as foundations for better design and assess next‐generation flux analysis techniques. Jiménez del Val et al (2023) propose a more compact network model, CHOmpact, that can provide improved interpretations from simulations, including the identification of shifts in key metabolic behaviors. This model could also serve as a platform for dynamic models used for process control and optimization.…”
Section: Improving Cho Cell Line Performance Through Cell and Bioproc...mentioning
confidence: 99%